Comparison of Implementation Tiny Encryption Algorithm (TEA) and Advanced Encryption Standard (AES) Algorithm on Android Based Open Source Cryptomator Library - Budiyanto, Dani; Putro, Prasetyo Adi Wibowo (2018 International Seminar on Research of Information Technology and Intelligent Systems (ISRITI), 2018)
Android based open source cryptomator library is an open source library created by Skymatic and published on the cryptomator.org page. This library uses the AES algorithm which has good speed but in some studies it still has problems in code size. Based on the results of a study in 2015, the Tiny Encryption Algorithm (TEA) algorithm was stated to be lighter and requires less code size than AES. Therefore, this study will compare the performance of the implementation of the TEA and AES algorithm Android-based library for cryptomator. Based on the results of a comparative study, the performance of the TEA algorithm implementation is better than AES seen from two parameters of performance testing, namely execution time and throughput.